S6K2: The Neglected S6 Kinase Family Member - Pardo, Olivier E.; Seckl, Michael J. (Frontiers in Oncology, 2013)
S6 kinase 2 (S6K2) is a member of the AGC kinases super-family. Its closest homologue, S6K1, has been extensively studied along the years. However, due to the belief in the community that the high degree of identity between these two isoforms would translate in essentially identical biological functions, S6K2 has been largely neglected. Nevertheless, recent research has clearly highlighted that these two proteins significantly differ in their roles in vitro as well as in vivo. These findings are significant to our understanding of S6 kinase signalling and the development of therapeutic strategies for several diseases including cancer. Here, we will focus on S6K2 and review the protein-protein interactions and specific substrates that determine the selective functions of this kinase.